Relationship between occupational hazards and pregnancy complications in health care workers in Gonabad University of Medical Sciences - MILAD naja_khajavian@yahoo.com; maryam Moaven Saeidi; NASIM khajavian (طب کار, 2023)
Aims: Reproductive disorders are mentioned as one of the ten main diseases and work-related injuries and working in the health care field may affect pregnancy and its complications .The aim of this study was to observe the adverse consequences of pregnancy between female health care workers in relation to Occupational risk factors